Deep freeze [large type] - Grumley, Michael C. (Grumley, Michael C. Revival series, 2025)
The accident came quickly. With no warning. In the dead of night, a precipitous plunge into a freezing river trapped everyone inside the bus. It was then that Army veteran John Reiff's life came to an end. Extinguished in the sudden rush of frigid water. There was no expectation of survival. None. Let alone waking up beneath blinding hospital lights. Struggling to move, or see, or even breathe. But the doctors assure him that everything is normal. That things will improve. And yet, he has a strange feeling that there's something they're not telling him. As Reiff's mind and body gradually recover, he becomes certain that the doctors are lying to him. One by one, puzzle pieces are slowly falling into place, and he soon realizes that things are not at all what they seem. Critical information is being kept from him. Secrets. Supposedly for his own good. But who is doing this? Why? And the most important question: can he keep himself alive long enough to uncover the truth?